KONSEP ADAT DALAM PERADABAN MELAYU - Naina, Siti Arbaina Juliana; Maryamah , Maryamah; Sartika, Sri Dewi; Neli, Neli (Jurnal Multidisipliner Kapalamada, 2023)
Comes from the Sanskrit budhayah, which is the plural form of the word buddhi which means budi or intellect. In English, the word culture comes from the word culture, in Dutch it is termed cultur, in Latin, it comes from the word colera. Colera means cultivating, working, fertilizing, developing land (farming) (Setiadi, et al, 2009: 27). According to Herkovits in Soekanto (1993: 162) to understand the essence of the nature of culture, it must be able to solve paradoxes in culture. The method used in this scientific journal is literature study, which is a series of activities related to library data collection methods, reading and recording, and processing research materials. The importance of adat in the life of the Malay people is that it functions to regulate almost all sides of life, providing direction and foundation in all activities, from the big things to the smallest things. Adat teaches people to be civilized, polite, tolerant, respectful, self-aware, helpful - in order to create an atmosphere of harmony and peace in the life of society, nation and state. In addition, Malay customs are sourced and refer to the teachings of Islam. Therefore, adat is used as the identity of every Malay person. In accordance with the teachings of Malay custom, if you want to know the glory of the people, look at their customs, language shows the nation, customs show the people. Adjudicated adat can thus be likened to 'implementing regulations' of a customary provision. Adjudicated adat is based on consensus and deliberation, but it must not contradict or deviate from the provisions of actual adat. Adjudicated adat will be changed if it is no longer in line with developments Adat emerges as the basic structure of all life and defines the personality traits of a society.